Educación y revolución cibernética - Villanueva Martínez, Orlando (Ingeniería, 1999)
Today's world has not stopped in a vertiginous carreer to reach the ideal of the automation, it is as well as the daily things have bean transformed by the age a bit. The microelectrónic revolution has been so much globalized that is generating in the different environments, mainly in the educational practice deep transformations and sociocultural impacts characterized by specialists on the topic as like a ciberculture. There is not doubt that the new images express at the same time two dimensions of the existence: tecnification, by one hand industrialization of the imaginary but also, at the same time, imaginary technocultural active, creative, able to speak culturally (and not only manipulate technically) the techniques and the procedures of the moment, to opening new spaces for the educational practice and time for a new age of the sensitive.